Evaluating Ethnic Disparities in Restrictive Practices in Broadmoor High Secure Hospital - Laura Gröger; Lauren Boniface; Susanna Martin; Saji Nabi (BJPsych Open)
Aims: Manual and mechanical restraint are restrictive practices that are applied as a last resort in a high secure psychiatric setting in order to manage risk to self, others and to deliver safe care. These interventions can have inherent risks to the physical and mental health of patients and staff. Previous studies have shown a discrepancy in the way patients from different ethnic backgrounds can experience restrictive practice in mental health care settings. This service evaluation aims to understand whether a patient’s ethnicity has an influence on the use of manual and mechanical restraint at Broadmoor High Secure Hospital by considering restraint variables alongside demographic and risk factors.